Verbal derived stems and semantics of prefixed verbs in the earliest Lithuanian texts - Vanhala, Otso (Lietuvių kalba, 2022)
This article discusses the deverbal verb derivation by the means of the prefixes in the Old Lithuanian language, basing on the corpus of about 110 primary verbs and their approximately 460 derivates attested in the Evangelijos bei epistolos (Gospels and Epistles, ViE) and the Catechism (ViC) of Baltramiejus Vilentas, with additional data from other Prussian Old Lithuanian sources up to the year 1600. By comparing the derived verbs with their bases occurring in the Old Lithuanian texts, the co-occurring morphological and semantical changes were found out. Attention is brought on the together co-occurring morphological and semantical changes used in deriving telic verbs from their often atelic bases, e. g. the loss of infinitive formants -ė- and -o-, as in giedoti ‘to sing’→ pragysti ‘to start to sing, to start to crow’, or the ablaut change in šaukti ‘to shout’ → prašukti ‘to cry out, to exclaim’. The change in telicity can be used to classify the derived verbs into aktionsart classes (e. g. ingressive/momentaneous, delimitative). The telic ingressive/momentaneous derivatives also have the nasal infix or -st- formant in the present tense. This article shows that the non-prefixed verbs with ingressive or momentaneous meaning of the type gysti occur extremely rarely in the oldest Lithuanian texts, and are better seen as later de-prefixed derivatives of the type pragysti, i.e. pragysti → gysti. Similarly, the derived type pragiedoti is rare in Old Lithuanian as the prefixation is usually accompanied by the shortening of the infinitive stems in the derivatives of this semantic class, leading to pragysti, although the type pragiedoti also occurs. This has led to the formal patterning of the derivatives and base verbs into two new models similar to that of degti → sudegti, the two new patterns showing only a simple prefixation: gysti → pragysti and giedoti → pragiedoti.